Studi Kelayakan Pabrik Gula Rafinasi dengan Kapasitas 100000 ton/tahun melalui Analisa Ekonomi - Aista Pudji Witari; Gistanya Lindar Anggraini; Erlinda Ningsih (Institut Teknologi Adhi Tama Surabaya, 2021)
Refined sugar is sugar that is produced from raw sugar through a refined processto remove impurities and molasses attached to Raw sugar. The process that will beused in the manufacture of refined sugar from raw sugar with carbonationpurification is divided into seven stages, namely: affination process, clarificationprocess, filtration process, decolorization process, evaporation process,crystallization process, drying process. The plant is planned to operate 300 daysper year with a capacity of 100,000 tons per year. The factory is planned to beestablished in Sambas Regency, West Kalimantan. From the results of theeconomic analysis obtained: Internal Rate Of Return (IRR) of 66%, Pay Out Time(POT) of 3.3 years, Break Even Point (BEP) of 36%. Based on the technical andeconomic analysis that has been carried out, it is feasible to establish a refinedsugar factory from raw sugar